Precision measurement of the Ξ0b baryon lifetime - Aaij,R; Abdelmotteleb,ASW; Abellan,Beteta C; Abudinén,F; Ackernley,T; Adefisoye,AA; Adeva,B; Adinolfi,M; Adlarson,P; Agapopoulou,C; Aidala,CA; Ajaltouni,Z; et al. (Physical Review D, 2025)
A sample of pp collision data, corresponding to an integrated luminosity of 5.4 fb−1 and collected by the LHCb experiment during LHC Run 2, is used to measure the ratio of the lifetime of the Ξ0b baryon to that of the Λ0b baryon, (Formula presented). The value rRun τ 2 ¼ 1.004 ± 0.009 ± 0.006 is obtained, where the first uncertainty is statistical and the second systematic. This value is averaged with the corresponding value from Run 1 to obtain rτ ¼ 1.004 ± 0.008 ± 0.005. Multiplying by the known value of the Λ0b lifetime yields τΞ0 ¼ 1.475 ± 0.012 ± 0.008 ± 0.009 ps, where the last uncertainty is due to the limited knowledge b of the Λ0b lifetime. This measurement improves the precision of the current world average of the Ξ0b lifetime by about a factor of two, and is in good agreement with the most recent theoretical predictions.